1999
DOI: 10.1002/(sici)1096-9861(19990301)405:1<45::aid-cne4>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Early induction of T?1 ?-tubulin transcription in neurons of the developing nervous system

Abstract: In this report, we have examined the relationship between the onset of neuronal gene transcription and neuronal development by characterizing expression of the early panneuronal Tα1 α‐tubulin promoter in developing neurons. In the peripheral nervous system, detectable expression of a β‐galactosidase transgene driven by the Tα1 promoter (Tα1:nlacZ) was coincident with neuronal birth dates, with the exception of sympathetic neuroblasts, which expressed the transgene prior to terminal mitosis. Similarly, in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 50 publications
4
73
0
Order By: Relevance
“…Some GFP-positive cells in the ONL also exhibited staining for the mitotic marker BrdU, suggesting that they might correspond to the previously described rod precursors (Otteson and Hitchcock, 2003). Neural progenitor cells have been reported to express ␣1-tubulin in the adult CNS of zebrafish and mammals (Wang et al, 1998;Gloster et al, 1999;Goldman et al, 2001). Whereas robust immunoreactivity for GFP was observed in WT retinal layers, none could be detected in fish carrying mutant promoters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some GFP-positive cells in the ONL also exhibited staining for the mitotic marker BrdU, suggesting that they might correspond to the previously described rod precursors (Otteson and Hitchcock, 2003). Neural progenitor cells have been reported to express ␣1-tubulin in the adult CNS of zebrafish and mammals (Wang et al, 1998;Gloster et al, 1999;Goldman et al, 2001). Whereas robust immunoreactivity for GFP was observed in WT retinal layers, none could be detected in fish carrying mutant promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of transgenic mice expressing a LacZ reporter gene under the control of the rat ␣1-tubulin promoter demonstrated that a 1.1 kb upstream sequence are sufficient for directing transgene expression in developing and axotomized motor and sympathetic neurons (Gloster et al, 1994;Bamji and Miller, 1996;Wu et al, 1997). The ␣1-tubulin promoter starts expressing as soon as neurons are born (Gloster et al 1999) and has subsequently been used for neural progenitor identification and isolation ; its activation via the C/EBP family of transcription factors was recently shown to contribute to the passage from progenitor to neuronal cell phenotype . Although transgenic mice have contributed significantly to our understanding of ␣1-tubulin promoter activity, fish models offer several unique advantages (Udvadia and Linney, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Such a difference could be predicted by considering the development of these two populations of neurons. Cortical neurons, like most CNS neurons, induce neuronal gene expression and undergo terminal mitosis at the same time (Gloster et al, 1999). Perturbation of this progenitor-topostmitotic neuron transition, for example, via functional inhibition of the pRb family (Slack et al, 1998) or via overexpression of Id2 (Toma et al, 2000), leads to cellular apoptosis; in no conditions yet reported do cortical cells divide while expressing a neuronal phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether similar mechanisms are essential for the transition from a cycling sympathetic neuroblast to a postmitotic sympathetic neuron. In fact, the mechanisms appear to be fundamentally different: sympathetic neuroblasts express a neuronal phenotype while still dividing (Rothman et al, 1978;Rohrer and Thoenen, 1987;Memberg and Hall, 1995), whereas most CNS progenitors express a neuronal phenotype only when they undergo terminal mitosis (Lauder and Bloom, 1974;Rothman et al, 1980;Koulakoff et al, 1983;Menezes and Luskin, 1994;Gloster et al, 1999).…”
mentioning
confidence: 99%
“…pRb becomes essential immediately after neuronal fate determination, and lack of pRb causes virtually all neuronal populations to undergo apoptosis (16,17). However, in mice with Rb specifically deleted in the CNS, some neuronal populations increase because of aberrant S-phase entry, and they appear to differentiate relatively normally without apoptosis (18)(19)(20).…”
mentioning
confidence: 99%